Identification of an intraspecific alarm pheromone and two conserved odorant-binding proteins associated with (E)-β-farnesene perception in aphid Rhopalosiphum padi. (August 2017) - Fan, Jia; Xue, Wenxin; Duan, Hongxia; Jiang, Xin; Zhang, Yong; Yu, Wenjuan; Jiang, Shanshan; Sun, Jingrun; Chen, Julian
Graphical abstract: Abstract: (E)-β-farnesene (EBF) is the common active component of aphid alarm pheromone. Either or both of two orthologs of ordorant-binding proteins (OBPs), OBP3 and OBP7, recently reported in aphids, may be involved in EBF perception. The aim of this study was to investigate the respondence of the aphid Rhopalosiphum padi to its intraspecific alarm pheromone and which OBP is responsible for that response. We tested the olfactory response of the aphid R. padi to EBF and freshly crushed aphids. Then, we extracted the volatiles from crushed aphids using solid phase microextraction (SPME) for analysis with GC × GC–TOF/MS. We also cloned two OBPs cDNAs in R. padi ( RpadOBP3 and RpadOBP7 ) and expressed them in competent Escherichia coli cells. Both recombinant proteins, RpadOBP3 and RpadOBP7, bound EBF well, with RpadOBP7 having specifically stronger affinity for EBF than for other volatiles. Based on the crystal structure of the OBPs with high identity, we performed homology modeling and analyzed the interactions between RpadOBPs and EBF. In conclusion, R . padi was repelled by both EBF and crushed aphids. EBF was identified as the only volatile that acted as the alarm pheromone. Our results indicated that OBP7 is a potential molecular target to control wheat aphids by disturbing their behaviors to the alarm pheromone.